Evaluation of Brand Equity for Automobile Car Industry: Perception of Customers in Karachi - Masood Hassan (International Journal of Experiential Learning & Case Studies, 2018)
Establishment of strong brand equity is now one of the most priorities to numerous Car Automaker companies, but achieving that objective is become difficult due to the reason that the services and products of several companies are homogenous and their ways of distributions channels are also similar. Nowadays, brand equity is one of the possible ways through that customers can discriminate one brand among others. By providing better brand perceptions, the companies could have satisfied base of consumers. In view of its significance, the study subjects to measure the brand image’s effects and the effects of brand loyalty, brand awareness, and perceived quality of the brand equity in automobile car sector of Karachi. Our findings confirmed about brand image, brand loyalty, brand awareness, and perceived quality that these mentioned attributes are the antecedents of brand equity for this research, revealing that increases in any of these variables would generate higher levels of brand equity. Results suggest that there will be larger impact of parameter brand image on the brand equity in the comparison with other parameters. This would carry the implication that a Car Auto Maker & Selling company if anxious to increase brand equity then it should try attempts to build customers’ brand image that may lead in generation of brand equity with higher levels.